Cancer-associated venous thromboembolism and the non-vitamin K antagonist oral anticoagulants: a review of clinical outcomes and patient perspectives. (1st November 2020) - Overvad, Thure Filskov; Larsen, Torben Bjerregaard; Søgaard, Mette; Albertsen, Ida Ehlers; Ording, Anne Gulbech; Noble, Simon; Højen, Anette Arbjerg; Nielsen, Peter Brønnum
ABSTRACT: Introduction: Cancer-associated venous thromboembolism remains an important but challenging aspect in the treatment of patients with cancer. Recently, alternatives to injection of low-molecular-weight heparin (LMWH) have been introduced, the non-vitamin K antagonist oral anticoagulants (NOACs), which could potentially alleviate patients from burdensome daily injections. Areas covered: This review discusses the available evidence exploring the role of NOACs in the treatment and secondary prevention of cancer-associated venous thromboembolism, from randomized trials, observational data, contemporary guideline recommendations, and patient perspectives. Expert opinion: Edoxaban, rivaroxaban, and apixaban have proven attractive alternatives to LMWH for the treatment of cancer-associated venous thromboembolism. Contemporary guidelines have promptly endorsed the use of NOACs in patients with most cancer types. Nonetheless, issues remain regarding bleeding risk, interactions with medical cancer treatment, and the effectiveness and safety for extended treatment periods. There are head-to-head comparisons of the NOACs, and therefore no data favoring the use of one NOAC over the others. Patient's preferences are highly diverse and should be part of routine considerations when weighing risks and benefits associated with various available anticoagulant drugs.